RAW264.7 대식세포에서 산양삼 추출물의 탐식능과 사이토카인 분비 증가에 의한 면역 활성 증진 효과 - 정재인(Jae In Jung); 김정미(Jung Mi Kim); 김희성(Hee Sung Kim); 김형서(Hyung Seo Kim); 김은지(Eun Ji Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구에서는 산양삼 추출물의 면역증진효능을 조사하기 위해 선천성 면역에 중요한 역할을 하는 대식세포를 이용하여 실험하였다. 마우스 대식세포인 RAW264.7 세포에 0, 25, 50 및 100 µg/mL로 처리한 경우 산양삼 추출물은 산화질소의 생성에 아무런 영향을 미치지 않았다. Zymosan 처리에 의해 활성화된 RAW264.7 세포의 탐식능은 산양삼 추출물 처리에 의해 현저히 증가하였다. 또한 산양삼 추출물은 대식세포에서 분비되는 사이토카인인 TNF-α, IL-6, IL-1β의 생성 분비를 대조군에 비해 농도 의존적으로 증가시켰다. 본 연구의 결과 면역반응 활성화를 위한 대식세포의 활성화에 산양삼 추출물이 매우 유용하게 사용될 수 있음을 제시한다. 본 연구 결과를 바탕으로 산양삼 추출물의 활성 물질에 대한 추가 연구 및 in vivo 후속연구를 통하여 산양삼 추출물의 면역증진에 대한 추가적인 기전연구가 필요할 것으로 생각된다. Cultivated wild ginseng is used as an herbal medicine because of its variety of pharmacological effects. This study examined the immunostimulatory effects of an aqueous extract of wild-cultivated ginseng extract (WCGE) on RAW264.7 mouse macrophages. The cytotoxicity, phagocytic activity, nitric oxide (NO) production, and production of cytokines in RAW264.7 cells were measured. WCGE increased the phagocytic activity of RAW264.7 cells significantly within the concentration range of 0 to 100 μg/mL. In addition, WCGE increased the production of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 significantly. On the other hand, WCGE had no effect on NO production of RAW264.7 cells. These results suggest that WCGE exhibits immunostimulatory activity by increasing the phagocytic activity and the production of TNF-α, IL-1β, and IL-6 in RAW264.7 cells. These findings highlight the potential of WCGE as an immunostimulatory agent. KCI Citation Count: 7